(untitled) (The Proceedings of The International Conference on Climate Change, 2019)
Climate change is causing loss of homestead and livelihood of the people of affected areas all over the world. They are being compelled to desert their homes and locality to secure self-existence and thus being displaced, which is known as climate displacement and these people are being marked as climate displaced persons. This study is aimed to ascertain vulnerability of climate displaced persons of Bangladesh and to discuss the measures essential to ensure their protection. It is an analytical and mixed method research having convergent and parallel design. Area of study was Chattogram or Chittagong District. Field study was comprised of a survey, case studies, FGD, KII and applications of right to information (RTI). Finding shows, in Bangladesh this community got no legal recognition by any parliamentary enactment. Though there are a few projects to facilitate people in distress which may provide for this community also, still, no criteria are specified to ascertain the beneficiaries. Steps should be taken to meet their immediate needs like foods, drinking water and sanitation; mid-term wants like alternative employment generation and long term protections like rehabilitation. Both government and non-government bodies should pursue the international community to attain a common consensus about this issue.